Exploring the early years needs of Venezuelan migrant children in Trinidad and Tobago. Issue 2 (3rd April 2022) - Adbul-Majied, Sabeerah; Kinkead-Clark, Zoyah
ABSTRACT: Since 2015, Trinidad and Tobago experienced an influx of over 40, 000 migrants from Venezuela. Having signed the Convention on the Rights of the Child and the Convention Relating to the Status of Refugees, young migrant children are entitled to education in Trinidad and Tobago. However, they face obstacles accessing schooling and social services [UNICEF EC (UNICEF Eastern Caribbean). 2019. "Making Friendly Spaces for Venezuelan Children." Accessed September 14, 2019. https://www.unicef.org/easterncaribbean/media_39482.html ]. Broadly, this conceptual study sought to answer one primary question: What are the key issues Trinidad and Tobago's government must address in order to support young children from Venezuelan migrant families in the early years setting? To answer this, data from policy documents, government releases, peer-reviewed articles and news reports were analysed. Six overarching themes emerged from the literature: policy gaps, fear/xenophobia, resource limitations, familial support, political risks and child rights infringements. Recommendations for overcoming challenges are included.